Shorter screw lengths in dynamic Dynesys fixation have less screw loosening: From clinical investigation to finite-element analysis. Issue 3 (17th December 2022) - Hsu, Fang-Chi; Chen, Chen-Sheng; Yao, Yu-Cheng; Lin, Hsi-Hsien; Wang, Shih-Tien; Chang, Ming-Chau; Liu, Chien-Lin; Chou, Po-Hsin
Abstract : Background: The dynamic Dynesys Stabilization System preserves lumbar mobility at instrumented levels. This study investigated the effect of screw length on screw loosening (SL) after dynamic Dynesys fixation and screw displacement during lumbar motion, using clinical investigation and finite-element (FE) analysis. Methods: Clinical data of 50 patients with degenerative spondylolisthesis treated with decompression and Dynesys fixation in 2011 were analyzed retrospectively. Horizontal sliding displacement and vertical displacement of screw tips at L4 were analyzed postoperatively using displacement-controlled FE analysis at the L4-L5 level with screw lengths 45 (long screw), 36 (median screw), and 27 (short screw), and 6.4 mm in diameter, under flexion, extension, lateral bending, and rotation. Results: In 13 patients (13/50, 26%), 40 screws (40/266, 15%) were loose at mean follow-up of 101.3 ± 4.4 months. Radiographic SL at 35, 40, 45, and 50 mm were 7.7%, 10.7%, 12.1%, and 37.5%, respectively, regardless of the fixation level ( p = 0.009). FE analysis revealed that the long screw model with corresponding longer lever arm had maximal horizontal sliding displacement under all directions and maximal vertical displacement, except for lateral bending. Conclusion: Shorter screws in Dynesys fixation may help avoid dynamic SL. Clinically, 50 mm screws showed the greatest SL and median screw screws demonstrated the least displacement biomechanically.